IMPROVEMENT OF METHODOLOGICAL TOOLS FOR FINANCIAL REHABILITATION OF INDUSTRIAL ENTERPRISES - A. N. Mironova (Стратегические решения и риск-менеджмент)
A methodology for developing a financial rehabilitation plan and a debts repayment schedule is presented, which may be applied during the procedure of financial rehabilitation of an organization engaged in the industrial sector. The structure of the financial rehabilitation plan and a template of the debts repayment schedule for industrial enterprises is presented, a developed algorithm with the formulae for calculation of precedence of repayment of the creditor’s demands in the form of a flowchart is presented, a formula for calculation of the total amount of the due debt is adjusted, and the feasibility of developing the financial rehabilitation plan is substantiated, whether or not the obligations performance is secured.